The implementation of health care aimed at the cessation of tobacco use, treatment of tobacco dependence and consequences of tobacco consumption in the Russian Federation - S. A. Boytsov; P. K. Yablonskiy; M. G. Gambaryan; O. A. Sukhovskaya; O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2016)
The summarizing of the experience of medical care at the cessation of tobacco use and the treatment of tobacco addiction and consequences of tobacco consumption in the Russian Federation (RF) as well as suggestions for their improvement are presented.For the effective implementation of health care, aimed at the cessation of tobacco use, treatment of tobacco addiction and consequences of tobacco consumption in the RF it is necessary to solve the following problems:to include doctors of all specialties in the process of medical care and treatment oftobacco addiction and consequences oftobacco consumption in the RF; to ensure effective implementation of the existing legal documents determining the procedure for providing medical aid, aimed at ending the use of tobacco, treatment of tobacco dependence and consequences of tobacco consumption, greater control over their performance and quality of their implementation; to expand of the network of medical offices for cessation of tobacco consumption on the basis of existing structures in primary health care settings (including women's and children’s outpatient clinics), as well as hospitals and health resorts, their provision of personnel and equipment, introduction of group forms of work; to ensure a permanent system of training on assistance at the cessation of tobacco consumption, the treatment of tobacco dependence and consequences of tobacco consumption, including the introduction of medical assistance cycle on cessation of tobacco consumption for student training in medical schools and programs for postgraduate education of health professionals